2022
DOI: 10.1109/access.2022.3210347
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Model for Hepatitis C Diagnosis Customized to Each Patient

Abstract: Machine learning is now widely used in various fields, and it has made a big splash in the field of disease diagnosis. But traditional machine learning models are general-purpose, that is, one model is used to evaluate the health status of different patients. A general-purpose machine learning algorithm depends on a large amount of data and requires abundant computing power support, relies on the average level to describe the model performance, and cannot achieve optimal results on a specific problem. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Although the research provided useful insights, potential biases or missing data could distort the findings [ 20 ]. The main challenges include the need for substantial computing power and the difficulty of implementing and maintaining tailor-made models in real-world healthcare environments [ 21 ]. Enhanced diagnostic capabilities for hepatitis based on a few features and effective class balancing with the synthetic minority over-sampling technique (SMOTE) strategy were among the reported benefits [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the research provided useful insights, potential biases or missing data could distort the findings [ 20 ]. The main challenges include the need for substantial computing power and the difficulty of implementing and maintaining tailor-made models in real-world healthcare environments [ 21 ]. Enhanced diagnostic capabilities for hepatitis based on a few features and effective class balancing with the synthetic minority over-sampling technique (SMOTE) strategy were among the reported benefits [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study showed that machine learning (ML) algorithms were able to predict advanced fibrosis in patients with AUCROC in the range 0.73-0.76 and with an accuracy of 66.3-84.4%, respectively. The CatBoost, XGBoost, RFGini, LightGBM, Random forest (RF), and KNN have been used in [11] to detect Hepatitis C patients The result showed that of all ML modes highest accuracy (0.9593), recall (0.6667), precision (1), and F1-score (0.7867) was achieved with XGBoost algorithm. In [12] the supervised learning (decision tree, logistic regression, KNN, Extreme Gradient Boosting, Gradient Boosting Machine, Gaussian Naive Bayes, RF, Gradient Boosting, SVM), and unsupervised learning (K-means, Hierarchical clustering, DBMSCN, Gaussian Mixture, and K-means) models were used to detect the Hepatitis C virus from a dataset containing laboratory data of Hepatitis C patients and blood donors.…”
Section: Introductionmentioning
confidence: 99%